Enabling Leadership Behaviours of Principals Leading Rural Primary Schools in the Ilembe District, South Africa - Ncokwana, Zamokwakhe Thandinkosi; Blose, Sibonelo (Studies in Learning and Teaching, 2025)
This paper flows from a research project that examined the Principals’ lived experiences of leading rural primary schools. It focuses specifically on leadership behaviours enabling the principals in leading rural primary schools against challenging contextual realities. The servant leadership concept was adopted to frame our understanding of and engagement with participants’ experiences. Regarding the research method, we employed the narrative inquiry design to inquire into principals’ experiences. In keeping with this design, we generated field texts using a narrative interview, an unstructured type of interview. The generated field texts were subsequently analyzed through narrative analysis and analysis of narratives. The findings revealed important leadership behaviours that appeared to enable the participating principals in leading rural primary schools; these include embracing all stakeholders as a family, leading a rural school as a servant, and leveraging stakeholder support to benefit learners. In conclusion, we deduce that the participating rural primary school principals keep their schools afloat by setting themselves as servants who show support to all stakeholders and who are willing to go out of their way to solicit charity to expand the support.